2017
DOI: 10.1038/s41598-017-05331-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent giant resistance anomaly in LaAlO3/SrTiO3 nanostructures

Abstract: The resistance of the electron gas (2DEG) at the interface between the two band insulators LaAlO3 (LAO) and SrTiO3 (STO) typically drops monotonically with temperature and R/T curves during cooling and warm-up look identical for large area structures. Here we show that if the LAO/STO is laterally restricted by nanopatterning the resistance exhibits a temperature anomaly. Warming up nanostructures from low temperatures leads to one or two pronounced resistance peaks between 50 and 100 K not observed for larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…In 2017 Goble et al demonstrated that the resistivity perpendicular to a domain wall is higher [12] than along the domain wall. Almost at the same time Minhas et al [13] showed an even more drastic effect on transport in LAO/STO nanostructures. They observed a resistance peak in 100nm wide LAO/STO channels around the phase transition temperature when warming up the structure.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In 2017 Goble et al demonstrated that the resistivity perpendicular to a domain wall is higher [12] than along the domain wall. Almost at the same time Minhas et al [13] showed an even more drastic effect on transport in LAO/STO nanostructures. They observed a resistance peak in 100nm wide LAO/STO channels around the phase transition temperature when warming up the structure.…”
Section: Introductionmentioning
confidence: 91%
“…The origin of the anomaly is often linked to structural phase transitions in the STO [9][10][11][12] but also alternative explanations were discussed [8]. In 2017 Minhas et al [13] showed that the resistance anomaly can also be observed in material grown at high oxygen pressure when a lateral confinement in a nanostructure exists.…”
Section: Introductionmentioning
confidence: 99%
“…The trapped single-vacancies and divacancies become mobile above 80 K and 176 K, which yields the conductivity recovery, separately. The reported cases 28,[32][33][34] are the patterned few layers LAO/STO in the length scale less than 10 mm, which means the interface is fully strained. When the number of LAO layers increases, the sample changes from fully strained state to partial strained state.…”
Section: Experiments Detailsmentioning
confidence: 98%
“…Because this two novel points are of the precise temperature interval it provides a potential temperature standard reference in the region of low temperature based on its resistance measurement and can be widely applied due to its larger scale. Minhas et al 34 made nano-patterned 6 u.c. layers LAO/STO samples and observed giant resistance anomaly.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Because this elongation is equally likely to occur along the x, y, or z axis, domains of differently oriented tetragonal unit cells emerge. These domains, and especially the walls forming between them, may have profound consequences for conductivity at SrTiO 3 surfaces (41)(42)(43)(44)(45)(46)(47). In the work described in this thesis, we find that two-dimensional models for conductivity apply to the data very well: the effect of these domain walls on our experiments appears to be negligible.…”
Section: Properties Of Bulk Srtiomentioning
confidence: 56%